Successful treatment of refractory seizures with phenobarbital, propofol, and medetomidine following congenital portosystemic shunt ligation in a dog. Issue 6 (18th December 2015) - Heidenreich, Dorothee C.; Giordano, Paola; Kirby, Barbara M.
Abstract: Objective: To report a case of refractory seizures following congenital portosystemic shunt (CPSS) ligation that regained normal neurologic and hepatic function with novel treatment. Medical care included constant rate infusions (CRI) of propofol and medetomidine in conjunction with phenobarbital and supportive intensive care. Case Summary: A 2‐year‐old neutered male Bichon Frise was diagnosed with a single extrahepatic CPSS based on typical clinical signs, laboratory data, abdominal ultrasound, and computed tomographic angiography. Following initiation of standard medical treatment, a complete surgical ligation of the CPSS was performed. Recovery was uneventful until postligation neurologic dysfunction developed 54 hours after surgery. Seizures were controlled with phenobarbital (6 mg/kg IM q 12 h) and propofol CRI (0.3–0.6 mg/kg/min). Attempts to wean the dog from the propofol CRI resulted in recurrence of seizure activity until the addition of medetomidine CRI (0.016 μg/kg/min) 76 hours after initiation of drug‐induced coma allowed gradual discontinuation of the propofol CRI. The dog regained full neurologic and hepatic function and had no further seizure activity apart from a small number of seizure episodes 5 and 22 months later. Adjustments in antiepileptic treatment resulted in no further neurologic dysfunction at 27‐month follow‐up. New or Unique Information Provided: This report highlights the potential benefit of medetomidine CRI for treatment of postattenuation refractory seizures, which to date have proven impossible to predict and difficult to treat with high mortality rates and persistent neurological deficits in surviving animals. Neuroprotective, drug‐sparing, and anti‐hypertensive features of medetomidine might improve outcome in postligation refractory seizures. Further investigation and clinical application of medetomidine CRI may improve outcome in this complication of CPSS attenuation.